Risk of Postoperative Bleeding in Tonsillectomy for Peritonsillar Abscess, as Opposed to in Recurrent and Chronic Tonsillitis-A Retrospective Study - Slouka, David; Čejková, Štěpánka; Hanáková, Jana; Hrabačka, Petr; Kormunda, Stanislav; Kalfeřt, David; Skálová, Alena; Šimánek, Václav; Kucera, Radek (International journal of environmental research and public health, 2021)
Tonsillectomy is a routine surgery in otorhinolaryngology and the occurrence of postoperative bleeding is not a rare complication. The aim of this retrospective, observational, analytic, cohort study is to compare the incidence of this complication for the most common indications. A group of patients indicated for tonsillectomies for peritonsillar abscess (group I) was compared to a group of patients indicated for chronic and recurrent tonsillitis (group II). There are a lot of pathophysiological differences in patients indicated for acute tonsillectomy for peritonsillar abscess and in patients indicated for elective tonsillectomy for chronic or recurrent tonsillitis. No technique to minimize the risk of bleeding after tonsillectomy has been found and a large part of postoperative bleeding occurs in postoperative home-care, which makes this issue topical. In total, 2842 unilateral tonsillectomies from the years 2014-2019 were included in the study. Bleeding occurred in 10.03% and, surprisingly, despite completely different conditions in the field of surgery (oedema, acute inflammation in peritonsillar abscess), there was no statistically significant difference between incidence of postoperative bleeding in the studied groups (p = 0.9920). The highest incidence of bleeding was found in the patients of group I on the eighth postoperative day, with those aged 20-24 years (p = 0.0235) being the most at risk, and in group II, on the sixth postoperative day, with those aged 25-29 years (p = 0.0128) and 45-49 years (p = 0.0249) being the most at risk.
Keywords: dospělí; Tonsillectomy; peritonzilární absces; peritonsillar abscess; tonzilektomie; Adult; mladý dospělý; postoperative bleeding; lidé; tonzilitida; chronic tonsillitis; Peritonsillar Abscess; kohortové studie; Cohort Studies; retrospektivní studie; Tonsillitis; Young Adult; recurrent tonsillitis; personalized treatment; Retrospective Studies; Humans